Punching shear analysis of slab-column connections - Moreno, Carlos (2014)
In this study, numerical simulations of the experimental behaviour of reinforced concrete slabs tested under punching by the authors are presented. The capabilities and limitations of the numerical model to reproduce the brittle shear failure are discussed.